Localization of cyclic GMP-dependent protein kinase and substrate in mammalian cerebellum. - Schlichter, D J (1980)
The regional and cellular distribution of guanosine 3',5'-cyclic monophosphate (cGMP)-dependent protein kinase (ATP:protein phosphotransferase,EC 2.7.1.37) in mammalian brain was examined by use of the photoaffinity label 8-azidoinosine 3',5'-cyclic monophosphate. Of the regions examined, cerebellum had by far the highest concentration of this enzyme. The cellular localization of cGMP-dependent protein kinase within the cerebellum was determined by examination of mutant mice missing specific types of cerebellar neurons. Mutant mice lacking Purkinje cells had greatly reduced amounts of cGMP-dependent protein kinase, whereas the loss of another cell type, granule cells, did not reduce cGMP-dependent protein kinase levels. By using the same strains of mutant mice, a 23,000-dalton soluble cerebellar substrate for cGMP-dependent protein kinase was also shown to be enriched in Purkinje cells. In contrast, the concentration of type I 3',5'-cyclic AMP-dependent protein kinase in the cerebellum was unaffected by the absence of Purkinje cells and only slightly reduced by the absence of granule cells. The enrichment in Purkinje cells of the cGMP-dependent protein kinase and its substrate suggests an important role for cGMP and cGMP-dependent protein phosphorylation in the function of this type of neuronal cell.